Marriage-versus-work concerns among the youth: an exploratory study in Malaysia - Qin, Jin (2018)
The study serves as a supplement to the current knowledge where sophisticated literature has shed light on the work-family conflict among married people, the youth, however, are absent from the existing research on the issue, especially under Malaysia context. The work-family conflict is not only facing the married group, but also the youth are aware of and experiencing the marriage-career conflict.